(untitled) (AYUSHDHARA, 2024)
Uterine fibroid is benign outgrowth and most common benign tumour in female, affecting millions of women worldwide. It is composed of smooth muscle and fibrous connective tissue, originated in muscle layer of uterus i.e., myometrium. 75% of fibroids are asymptomatic and painless. In Ayurveda, Acharya mentioned Granthi in which they explained that the glandular or nodular swelling caused due to vitiated Vatadi dosha and contaminated Mamsa, Rakta, Kaphanubandhita Meda known as Granthi. From all types mentioned in Samhita, Mamsaj Granthi can identically correlated with uterine fibroids. A review of Ayurvedic Samhita, modern text books, web sources and previous researches were used to collect data. The main goal of Ayurvedic management in Granthi is Samprapti bhanga of Granthi. References on this condition are limited in Ayurveda texts, as there is not such specific description given about the Garbhashaya Granthi. This study was aimed to collect research and concept evident to justify uterine fibroids, with the most similar diseases and their treatment described in Ayurveda. So that we can collectively get the effective route and forms of treatment and to get successful results in uterine fibroid by Ayurvedic management. This article explores the effectiveness of Ayurvedic treatment for uterine fibroids and compares it with various modes of Ayurvedic interventions.